33.6k views
2 votes
Simplify 32 ⋅ 35. (4 points)

37

310

97

910

User Alebon
by
4.8k points

1 Answer

3 votes

Explanation:

Did you mean.


= {3}^(2) * {3}^(5)


= {3}^(2 + 5)


= {3}^(7)

The answer is A.

If you want to work this question, you have to know about the formula to evaluate the exponential form above. This is the formula to evaluate the exponential form above.


  • {a}^(m) * {a}^(n) = {a}^(m + n)

User Shuvo Amin
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.